The Influence of Use Benefits, Convenience, Discounts, Security and Risk on the Intention To Use Indonesian Digital Wallets (DANA) In Bandar Lampung - Hanner Rambe; Satria Bangsawan (International Journal of Regional Innovation, 2023)
Technological developments, especially in electronic payment systems, continue to increase both in terms of increasing value and transaction volume due to the support of information and communication technology which is continuously developing. Digital wallet payments have become popular and most accepted as an emerging payment method in both developed and developing countries. Digital wallets continue to grow and continue to increase due to many factors, one of which is due to the recent Covid-19 Pandemic, the World Health Organization (WHO) recommends reducing physical activity, keeping a distance or physical distancing so that many consumers are inspired to carry out activities minimum physical contact. DANA digital wallet comes with an open-platform concept, both offline and online, but still integrated. DANA pursues a strategy to accelerate growth by providing cashback and sizable promos, while other payment applications generally incur administration fees when making transactions, especially bank transfer transactions. Other payment applications are also not as complete as DANA in providing easy access for their users, such as purchasing tickets for various entertainment platforms and making donation transactions to various charitable institutions. With this event, the researcher wants to know more deeply about how much influence respondents and customers have in intending to use the DANA application. The purpose of this study is to identify the effect of perceived benefits, convenience, discounts, safety and risks on intentions to use the DANA application. This research is a quantitative research using survey techniques with the subject of DANA application users in the city of Bandar Lampung. The data collection technique used a questionnaire in the form of a list of questions that were distributed online via Google form to respondents with a sample of 180 respondents. Based on the results of the study it is known that there is an influence between the benefits of use, safety of use, discounts and perceived risk of use partially on the intention to use the application of funds.